La mise en concurrence des systèmes juridiques nationaux et l’idée de Constitution économique - Salah, M. Mahmoud Mohamed (The Idea of Economic Constitution in Europe, 2022)
Conséquence de la compétition que les États se livrent pour attirer le maximum d’investisseurs, la mise en concurrence des systèmes juridiques nationaux s’est traduite par une libéralisation continue du droit qui a eu un effet direct sur l’idée de Constitution économique. Celle-ci a non seulement vu son épaisseur normative se renforcer du fait de la neutralisation des dispositifs juridiques dirigistes mais elle s’est également universalisée en raison de la conversion de la quasi-totalité des pays au dogme de « l’attractivité ». Toutefois, ce mouvement généralisé vers le tout libéral commence à être remis en cause sous l’effet de facteurs divers qui se traduisent par une demande sociale et politique pour plus de régulation étatique. Il en résulte à la fois un regain de l’unilatéralisme qui affecte la force des principes qui sous-tendent l’idée de constitution économique et une prise en compte plus affirmée des valeurs et intérêts collectifs qui altère la substance de ces principes.
Section: The Idea of Economic Constitution in Europe
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism